Pengaruh Corporate Social Responsibility, Green Accounting, dan Struktur Modal terhadap Profitabilitas Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Septa Aulia Dwi Andini; Vhika Meiriasari; Mutiara Kemala Ratu (Balance : Jurnal Akuntansi dan Bisnis, 2026)
The purpose of this research is to examine the effect of Corporate Social Responsibility (CSR), Green Accounting, and Capital Structure on the profitability of energy sector companies listed on the Indonesia Stock Exchange during 2022-2024. This research uses a quantitative approach based on annual and sustainability reports. The results show that, simultaneously, CSR, Green Accounting, and Capital Structure have a significant effect on profitability. Partially, CSR and Green Accounting do not significantly affect profitability, indicating that social and environmental aspects have not directly impacted short-term profits. Meanwhile, Capital Structure significantly affects profitability, making financing decisions an important determinant of financial performance. These findings suggest that the benefits of sustainability practices tend to appear in the long term. This study contributes to the literature on sustainability accounting and financial management, especially regarding factors influencing profitability in energy sector companies.